Current driven spin oscillation in PMA/IMA composite nanowires—a novel spin torque based nano-oscillators. (15th March 2019) - Yin, H; Lu, Z; Chen, C; Li, S; Wang, W; Li, C; Cheng, M; Zhang, Z; Xiong, R
Abstract: The spin dynamics in composite nanowires possessing both perpendicular magnetic anisotropy and in-plane magnetic anisotropy (IMA) regions are studied. It is found that, driven by proper currents, spin waves can be excited and propagate along the nanowires, leading to sustained oscillations of the magnetic moments. The frequency and amplitude strongly depend on the length of the longitudinal magnetized part ( L IMA ), and can be effectively tuned by applied current. The assistance of an applied field may help to obtain large frequencies and amplitudes simultaneously. Considering their ease of manufacture, these kinds of composite nanowires hold great promise for nano-oscillator applications.